Lepkosprężysta Powłoka Walcowa na Podłożu Lepkosprężystym o Jednokierunkowej Charakterystyce - Skalmierski, B.; Czogała, E. (Engineering Transactions, 1966)
This paper is devoted to the problem of bending of a viscoelastic circular shell resting on a foundation having viscoelastic properties in a single direction. It is assumed that the shell is loaded by radial forces only. The problem is considered in two variants: as a quasi-static and dynamic problem, the inertia forces being taken into consideration in the latter. Methods of integral transformations are used, the Laplace transformation in particular. The solution is obtained on the grounds of the elastic-viscoelastic analogy [3, 4, 5]. Special emphasis is laid on numerical computations, which concern the quasi-static problem for a radial force travelling along the periphery of a closed cylindrical shell. The Voigt rheological model is assumed in detailed considerations for both the shell and the foundation.